The deconstruction of the other man: towards a manifestation of god beyond the Ontometaphysical system of signification - Brower Beltramin, Jorge (Escritos, 2010)
Deconstruction allows us to position ourselves at the limit of the textuality articulated from the onto-metaphysical logos. It constitutes a comprehensive reading platform of language that searches, in its metaphorical expression, the nomination and renomination of Being, a deferral of its existence, beyond the logocentric systems of signification. This limit reading is assumed as a journey across the vast metaphysical discursive field with the intention of, finally, moving from the ontometaphysical systems of signification to face the Unnamable God, manifest in the other man, who, thrown into existence, claims ourresponsibility in view of his deep and permanent state of vulnerability.
Keywords: Desconstruction; the other man; God; Derrida